ChPDIA3 targeted by miR-126-x and miR-21-y responds to Vibrio harveyi infection in Crassostrea hongkongensis - Hou, Yongkang; Zhang, Fangqi; Liu, Xiaokun; Huang, Dongming; Li, Zhimin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe Hong Kong oyster (Crassostrea hongkongensis), as the main marine aquaculture shellfish in the South China Sea, not only has high economic and ecological value, but also is an ideal model for conducting research on pathogen-host interactions. In the cultivation process of C. hongkongensis, there is a challenge posed by vibrios. To improve the antibacterial strains of C. hongkongensis, we have studied the gene associated with immunity, PDIA3. Methods and findingsIn this study, we cloned the PDIA3 sequence of the C. hongkongensis, using the RACE technique. It has a total of 2081 bp and contains a 5'-UTR of 55 bp and a 3'-UTR of 547 bp. The ChPDIA3 gene sequence has an ORF frame that is 1479 bp in length and encodes 492 amino acids. Analysis of the phylogenetic tree constructed by Neighbor Joining method showed that ChPDIA3 clustered with other shellfishes into a single unit, which was consistent with the law of species evolution. DiscussionThe highest expression of ChPDIA3 was detected in gill tissues of the C. hongkongensis using RT-qPCR, and significantly higher expression in V. harveyi and LPS infection than Poly(I:C) (P<0.05). This may indicate that ChPDIA3 is primarily involved in the immune response against bacterial infections in the C. hongkongensis. The binding sites of miR-126-x, miR-21-y and ChPDIA3 were detected using dual luciferase experiments, respectively. The results showed that both miR-126-x and miR-21-y inhibited the 3'-UTR region of ChPDIA3. This suggested that both miR-126-x and miR-21-y inhibited ChPDIA3 expression. This study will help to further understand the function of ChPDIA3 in response to pathogen infection, thus providing new ideas for understanding the resistance and adaptation of the C. hongkongensis to Vibrio infection.